2020
DOI: 10.1111/eos.12745
|View full text |Cite
|
Sign up to set email alerts
|

Effect of essential oils on oral halitosis treatment: a review

Abstract: Halitosis is a very common condition which may affect up to 30% of the population. In about 90% of the cases, halitosis originates in the mouth due to inadequate plaque control, periodontal disease, dry mouth, faulty restorations, and in particular due to excessive bacterial growth. Oral malodor is mainly caused by a microbial degradation of amino acids into volatile, bad-smelling gases (volatile sulfur compounds-VSCs). Management of oral malodor is directed primarily at managing and reducing the VSC-producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 94 publications
0
22
0
Order By: Relevance
“…Many studies have been published on the inhibition of harmful oral bacteria for oral health [10,11,12,13]. In spite of the fact that antibiotics, including penicillin, erythromycin, and tetracycline are effective in the prevention of oral disease, they have not been utilized in humans due to increased antibiotic resistance after long-term use [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been published on the inhibition of harmful oral bacteria for oral health [10,11,12,13]. In spite of the fact that antibiotics, including penicillin, erythromycin, and tetracycline are effective in the prevention of oral disease, they have not been utilized in humans due to increased antibiotic resistance after long-term use [14].…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the fact that antibiotics, including penicillin, erythromycin, and tetracycline are effective in the prevention of oral disease, they have not been utilized in humans due to increased antibiotic resistance after long-term use [14]. Other studies have sought to inhibit oral periodontal bacteria using natural materials [13,15,16], inhibit GTase activity involving sucrose glucan formation [17], or use sucrose-alternative sweeteners that S. mutans are unable to metabolize [18]. Zinc ions, chlorhexidine (CHX) and cetylpyridinium chloride (CPC) and metal salts have been found to be effective in inhibiting the growth of halitosis-causing bacteria or in reducing the production of volatile sulfur compounds.…”
Section: Introductionmentioning
confidence: 99%
“…After 5 min of essential oil treatment, the strength of the bad smell was significantly lowered. This study showed that, besides the antimicrobial activity, essential oils can also control bad oral smell [ 26 ].…”
Section: Herbal Remedies For Dental Diseasesmentioning
confidence: 99%
“…The principle components responsible are benzyl alcohol, geraniol, eugenol, hydroxyl-citronellal, etc. Subsequently, the use of high concentrations/doses of essential oils can trigger adverse reactions [ 26 ]. Various factors, such as the amount of biological content, source of the material, and the route of exposure, should also be taken into consideration with regard to irritation potential.…”
Section: Challenges Of Herbal Therapiesmentioning
confidence: 99%
See 1 more Smart Citation